The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.31729/jnma.5424
|View full text |Cite
|
Sign up to set email alerts
|

Endodontic Indications among Patients Visiting a Tertiary Care Center: A Descriptive Cross-sectional Study

Abstract: Introduction: Endodontics is the study of prevention, diagnosis and treatment of diseases or injuries to the dental pulp. The ultimate goal of modern dental care is tooth preservation and root canal therapy/treatment is an available therapeutic strategy to retain teeth. The aim of the study is to find the prevalence of patients visiting a tertiary care center who had endodontic indications. Methods: A descriptive cross-sectional study was conducted over one year from April 15, 2020, to February 15, 2021 at a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…9 Additionally, hypersensitivity to dental pain might have driven them to see health care. 12 Similar trend was observed in various other studies [13][14][15] which reported a higher demand of root canal treatment by female patients. However, some studies [16][17][18] reported a higher demand in males.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…9 Additionally, hypersensitivity to dental pain might have driven them to see health care. 12 Similar trend was observed in various other studies [13][14][15] which reported a higher demand of root canal treatment by female patients. However, some studies [16][17][18] reported a higher demand in males.…”
Section: Discussionsupporting
confidence: 86%
“…This pattern is similar to other published literatures. 13,16,17,25 It has been found that general dentists are more comfortable doing RCT on anterior teeth and they refer posterior teeth needing RCT to the tertiary care centers to be performed by postgraduate residents and consultants. 17 However, another study 20 found high prevalence of endodontic treatment done on anterior teeth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation